High dose proton implantations into silicon: a combined EBIC, SRP and TEM study. Issue 11 (8th August 2014) - Kirnstoetter, Stefan; Faccinelli, Martin; Gspan, Christian; Grogger, Werner; Jelinek, Moriz; Schustereder, Werner; Laven, Johannes G.; Schulze, Hans‐Joachim; Hadley, Peter; Pizzini, Sergio; Kissinger, Gudrun
Abstract Proton (H+) implantations are used in power semiconductor devices to introduce recombination centers (Hazdra et al., Microelectron. J. 32(5), 449–456 (2001)) or to form hydrogen related donor complexes (Zohta et al., Jpn. J. Appl. Phys. 10, 532–533 (1991)). Proton implantations are also used in the 'smart cut' process to generate defects that can be used to cleave thin wafers (Romani and Evans, Nucl. Instrum. Methods Phys. Res. B 44, 313–317 (1990)). However, the implantation damage resulting from H+implantations is not completely understood. In this study, protons with energies from 400 keV up to 4 MeV and doses up to 1016 H+/cm² were implanted into highly ohmic boron doped m:Cz silicon (100). Electron Beam Induced Current (EBIC) measurements were performed to locally determine the minority charge carrier diffusion length. The diffusion length decreases with increasing implantation dose and incorporated damage. Spreading Resistance Profiling (SRP) measurements were performed to analyze the charge carrier concentration profiles for different annealing procedures. The electrical activation and growth of the defect complexes varies strongly with the annealing parameters. Transmission Electron Microscopy measurements were made to investigate the microscopic structures formed by the high dose implantation processes. Due to the high local damage density resulting from low energy and high dose H+ implants, platelet structures are formed. During high‐energy high‐dose H+implantations, the implanted hydrogen generates strain in the crystal lattice resulting in changes in the distances between atomic planes. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)